(untitled) (Perioperaciina Medicina, 2022)
Piperacillin/tazobactam represents a combination of the ureidopenicillin and the lactamase inhibitor. The antibiotic is the drug of choice for the treatment of severe infections, primarily in surgical and intensive care units. The area of clinical use of piperacillin/tazobactam includes intra-abdominal infections, skin and soft tissues infections, late nosocomial pneumonias, including ones in the context of the covid -19 pandemic, and infections of other localizations. The effectiveness of the intervention increases with intravenous administration of the drug by the method of prolonged infusions. A high susceptibility of most causative pathogens of wound infection to piperacillin/ tazobactam has been established in Ukraine (with the exception of Klebsiella spp. and non-fermenting bacteria). The drug can be used in patients with a history of allergic reactions to lactams; preliminary allergological testing is indicated only in cases of allergy to aminopenicillins and aminocephalosporins. The first domestic piperacillin/tazobactam under the name Refex is registered on the Ukrainian market.